2011
DOI: 10.1021/am201020q
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Activity of Heterostructures Based on TiO2 and Halloysite Nanotubes

Abstract: A one-step solvothermal method was used to prepare TiO(2)/halloysite composites. TiO(2) nanoparticles were deposited on the platform of the halloysite nanotubes (HNTs). XRD, FT-IR, FE-SEM, and TEM were applied to investigate the structures and morphologies of the resultant samples. The as-prepared TiO(2)/HNTs photocatalyst exhibits pH sensibility on the degradation of methanol and a higher photocatalytic activity on the degradation of acetic acid. The combination of the photocatalytic property of TiO(2) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(119 citation statements)
references
References 36 publications
8
111
0
Order By: Relevance
“…64 Ag nanoparticles were successfully immobilized on halloysite by dispersing the nanomaterial in an aqueous solution of precursor AgNO 3 and followed by a reduction reaction in the presence of reductants such as NaBH 4 or polyols.…”
Section: Support For Metal Nanoparticlesmentioning
confidence: 99%
“…64 Ag nanoparticles were successfully immobilized on halloysite by dispersing the nanomaterial in an aqueous solution of precursor AgNO 3 and followed by a reduction reaction in the presence of reductants such as NaBH 4 or polyols.…”
Section: Support For Metal Nanoparticlesmentioning
confidence: 99%
“…TiO 2 /HNT nanocomposites were synthesized according to a procedure reported in the literature [30]. The precursor solution was prepared by dissolving 2 mL of Titanium-n-butoxide in 40 mL of isopropanol.…”
Section: Synthesis and Characterization Of Tio 2 /Hnt Compositesmentioning
confidence: 99%
“…In this study, however, halloysite nanotubes (HNTs) with the chemical composition of (Al 2 Si 2 O 5 (OH) 4 ·2H 2 O) were used as support. Previous research works have reported the promising supporting abilities of this two-layered aluminosilicate clay due to the inherent hollow nanotube structure, large surface area, and their different outside and inside chemistry [29,30]. In addition, HNTs offer the following benefits such as hydrophilicity, good stability, high rejection against organic solvents and ease of disposal or reusability that are needed for membrane making [31].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid pace of industrial and economic development has increased our demands for energy as well as heightened our awareness of the accompanying environmental problems [1,2]. Semiconductor photocatalysis utilizing solar energy has attracted extensive attention because it is regarded as one of the most effective technologies to potentially address both energy and environmental issues [3,4].…”
Section: Introductionmentioning
confidence: 99%